Applying dental implant therapy in patients with oral lichen planus: a review of literature - Farnoosh Razmara; Mina Khayamzadeh; Ghazal Shabankare (SpringerOpen, 2020)
Abstract Lichen planus (LP) is a violent, paranormal inflammatory disease that can affect the skin or any lining of the mucous membrane. LPs are a branch of immune-mediated inflammatory disease (IMID) that collaborates with the function and structure of the immune system that are precipitated through various etiological infectious agents. Oral lichen planus (OLP) is one of the most common kinds of IMID. These traumas might limit the normal life of patients and, in some cases, can be treated spontaneously. In patients who are affected by OLP, the dental clinicians must be capable of the proper diagnosis of the disorder. Dental implants are progressively applied for the treatment of partial or complete edentulism. Implant rehabilitation in OLP patients is one of the main challenges for patients and dental clinicians. There is not enough knowledge about this condition, and also medical documents are limited. In this study, by conducting a comprehensive review of literature, we tried to collect related data around the safety and success rate of implant rehabilitation in patients who suffer from OLP disorder. There proved to be no relation between implant survival rate and OLP diseases, but it is proven that some factors such as bone quality and fracture resistance, parafunctional habits, and resection of the marginal mandible could powerfully affect it. For evaluation of the advantages and disadvantages of applying implants in patients with OLP disorders, implementation of controlled studies is required.